1998
DOI: 10.1074/jbc.273.50.33848
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of the Human β4-Integrin Gene Promoter and Enhancers

Abstract: The cell-surface adhesion molecule ␣ 6 ␤ 4 -integrin is a receptor for laminins and a component of hemidesmosomes. ␤ 4 -Integrin expression is restricted to proliferating basal keratinocytes in the epidermis and is suppressed when differentiation commences. Altered ␤ 4 -integrin expression levels correlate significantly with the aggressive behavior of cancers. In order to clarify the mechanisms that regulate transcription of the ␤ 4 -integrin gene, we cloned its 5-flanking region. This 5-flanking region was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 48 publications
3
45
0
Order By: Relevance
“…1A). In pursuit of a mechanism to account for this differential localization, we observed that the proximal promoter region of the mouse β4 gene (Takaoka et al, 1998) contains a CpG island that extends into the first exon (Fig. 1C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). In pursuit of a mechanism to account for this differential localization, we observed that the proximal promoter region of the mouse β4 gene (Takaoka et al, 1998) contains a CpG island that extends into the first exon (Fig. 1C).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a high GC content in the β4 promoter was observed in its original cloning 10 years ago, but the possibility of epigenetic regulation was not pursued (Takaoka et al, 1998). We were struck by the presence of a large CpG island in our analysis of this promoter, an observation that provided the impetus for this study.…”
Section: Discussionmentioning
confidence: 99%
“…Promoter studies of other integrins, such as ␣2, ␣3, ␣5, ␣6, ␣11, ␣IIb, ␤4, ␤5, CD11␤-␦, and CD18, have shown requirements for Sp1/Sp3 and/or AP-1 transcription factors and their cognate sites for expression (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(77)(78)(79). In particular, the promoter of ITGAV (integrin ␣v), the gene that encodes the heterodimerization partner of integrin ␤8, is also regulated by Sp1 and Sp3 (65).…”
Section: Discussionmentioning
confidence: 99%
“…There have been relatively few attempts to understand how epidermal integrin and ECM gene expression is regulated at the transcriptional level (Corbi et al 2000;Turner et al 2006;Takaoka et al 1998). However, one aspect that has been explored is negative regulation of integrin, cytoskeleton, and ECM genes by Myc Berta et al 2010).…”
Section: Integrins and Ecm Proteins As Epidermal Stem Cell Markersmentioning
confidence: 99%